Epidemiology of partial urorectal septum malformation sequence (or 'persistent cloaca'): A population-based study in seven regions of England and Wales, 1985-2010 - Tennant, P; Glinianaia, S; Wellesley, D; Draper, E; Kurinczuk, J; Tonks, A; Tucker, D; Wreyford, B; Rankin, J (BMJ Publishing Group, 2014)
Background: Partial urorectal septum malformation (pURSM) sequence (or 'persistent cloaca') is a rare congenital anomaly characterised by a joining of the urethral, anal, and genital openings into a single common channel. This study describes the epidemiology of pURSM sequence in England and Wales including prevalence, additional anomalies, and pregnancy outcomes. Methods: All cases of pURSM sequence prospectively notified to seven congenital anomaly registers in England and Wales during 1985-2010, whether delivered as live births, spontaneous fetal deaths (≥20 weeks' gestation), or elective terminations of pregnancy for fetal anomaly (TOPFA, any gestation), formed this population-based cohort. The risks of spontaneous fetal and infant death were examined by Kaplan-Meier analysis. Differences in prevalence over time, and between regions, were examined by multilevel Poisson regression. Results: 117 cases were recorded among 4 251 241 total births. Six (5%) pregnancies resulted in spontaneous fetal deaths, 53 (45%) in TOPFA, and 58 (50%) in live births. The prevalence was 2.8 (95% CI 2.3 to 3.4) per 100 000 total births, increasing significantly over time (p=0.002) and differing significantly between regions ( p=0.005). 77 cases (66%) had at least one additional major congenital anomaly outside the perineum, including 67 (57%) renal, 29 (25%) musculoskeletal, 26 (23%) digestive system, and 24 (21%) cardiovascular anomalies. The risks of spontaneous fetal and infant death were estimated as 8.9% (95% CI 4.1 to 18.8) and 26.3% (95% CI 15.1 to 43.4) respectively. Conclusions: This is the largest study of the epidemiology of pURSM sequence. The information will be valuable for families and health professionals whenever a case of pURSM sequence is diagnosed.